(untitled) (GAIMS Journal of Medical Sciences, 2023)
Background Mucor mycosis is an emerging dreadful opportunistic angio-invasive fungal infection occurring predominantly in immunocompromised individuals. Popularly known as “Black fungus”, it gained popularity due to its association with SARS-COVID-19. The aim of this study was to analyse various predisposing factors and histopathological features of COVID associated Mucor mycosis. Methodology This was a cross sectional retrospective study conducted at Department of Pathology, Government Kilpauk Medical College and Hospital, Chennai, over a period of six months, from April 2021 to September 2021. Maxillectomy and functional endoscopic sinus surgery (FESS) samples from 123 post COVID-19 patients were included in the study. Clinical details of systemic hypertension, diabetes, steroid and oxygen therapy were retrieved from case records. Results Our study comprised of 82 males and 41 females with male to female ratio of 2:1. Maximum number of cases were observed in the age group of 40 to 50 years (39%). Youngest patient was of 27 years and oldest age was 80 years. Facial pain was the most common symptom noted. In our study, 112 cases (91%) were diabetic, 71 cases (57.7%) were hypertensive and 116 cases (94.3%) had received systemic steroid therapy. Histopathological examination revealed increased fungal load with neutrophilic inflammation in 105 cases (85.36%), granulomatous inflammation in 18 cases (14.63%), mucosal invasion in 90 cases (73.17%), angioinvasion in 71 cases (57.7%), necrosis in 73 cases (59.3%) and infarct in 19 cases (15.6%). Conclusions Histopathological features such as high fungal load, angioinvasion and extensive areas of necrosis plays an important role in accurate diagnosis, assessing the prognosis and thereby reducing mortality and morbidity. We also conclude that high clinical suspicion in individuals with diabetes and steroid use is essential to facilitate early diagnosis and optimizing prompt treatment.